Makran ophiolitic basalts (SE Iran) record Late Cretaceous Neotethys plume-ridge interaction. Issue 13 (21st September 2020) - Esmaeili, Rasoul; Xiao, Wenjiao; Ebrahimi, Mohammad; Zhang, Ji'En; Zhang, Zhiyong; Abd El-Rahman, Yasser; Han, Chunming; Wan, Bo; Ao, Songjian; Song, Dongfang; Shahabi, Shirin; Aouizerat, Arthur
ABSTRACT: The Makran complex in southeast Iran provides a spectacular subduction-related accretionary complex to understand the mechanism of oceanic accretion and the evolution of subduction zones. In this paper, we present new major and trace element data as well as isotopic compositions of mafic volcanic blocks from the Makran ophiolitic mélange complex (OMC). Our aim is to assess the genesis of these rocks and discuss their implications on the evolution of Neotethys Ocean. These volcanic blocks are composed mainly of basalts with minor trachytes. The Makran lavas are occasionally interlayered with tuff layers. Zircons from these tuffs give U-Pb ages of 95 Ma, which is well in accordance with the reposted microfossil data for the interlayered pelagic limestones with pillow lavas. Makran basalts can be geochemically subdivided into four groups; normal to transitional MORB, enriched-MORB, Plume-type MORB and alkaline (-OIB-like) basalts. The OIB-like pillow lavas are represented by high values of Th/Tb (6.3–7.4) which are higher than other basalts (group 1 = 0.3–0.8; groups 2 = 0.7–1.6; group 3 = 1.58–1.36). 143 Nd/ 144 Nd(t) ratios for basalts ranges from 0.51247 to 0.51292, whereas 87 Sr/ 86 Sr(t) isotopic composition of the OMC lavas varies from 0.704433 to 0.709466. The Pb isotopic composition of the lavas are quite high, ranging from 15.49–15.66 for 207 Pb/ 204 Pb(t), 18.09–19.12 for 206 Pb/ 204 Pb(t) and 37.80–39.23 for 208 Pb/ 204 Pb(t) . The chemistry of these rocks suggests that they were formed most likely in an oceanic setting with clear plume-ridge interaction. These rocks can form from partial melting of a highly heterogeneous mantle source, which is extensively metasomatized with deep mantle OIB-type components. We suggest these rocks have been generated in an oceanic ridge with plume-ridge interaction, similar to the Iceland-Reykjanes Ridge, before being fragmented and accreted into the Makran accretionary complex. Graphical Abstract: uf0001